The empirical study of the relationship between external executive compensation gap and enterprise innovation investment - Evidence from Chinese Science Technology and Innovation Board companies - Huang, Yu (2022)
An important topic that has been addressed for a while in both academic and practical circles is how to use compensation agreements to incentivize Executives to engage in innovative activities. Based on social comparison theory, this paper selects a sample of emerging technology companies in China's Science Technology and Innovation Board from 2019 to 2021 to study the relationship between the external executive pay gap and enterprise innovation investment. And based on agency theory, the moderating effect of corporate directors' governance capability on this relationship is investigated. It has been discovered that the external executive salary gap can encourage businesses to invest in innovation when the average executive compensation of firms is higher than the industry average, and the positive incentive effect is enhanced by the high level of director governance ability. When the average executive compensation of firms is below the industry average, the external executive pay gap inhibits enterprises' innovation investment, and the high level of director governance strengthens this inhibiting effect. This suggests that Chinese technology-based innovative firms wanting to increase their investment in innovation also need to find the right balance between executive compensation and industry averages, while also paying attention to how directors govern them and the effects this brings. This paper not only elaborates on the external pay gap's economic repercussions but also offers suggestions for how businesses might modify their compensation policies and incentivize CEOs to foster company innovation.